FRANSUZ TILIDA “AYOL” LINGVOMADANIY KONSEPTINING YADRO VA PERIFERIYASI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article deals with the core and periphery of the “feminine” linguistic concept, reflecting in french linguistics on the meaning, the semantic field, of the “feminine” concept. There are also references to lexical and semantic representations of the concept.
Keywords: concept, core, semantic field, periphery, conceptuosphere, lexeme, linguoculture.